Spectrum of Clinical and Hematological Changes in Patients of Malaria: A Tertiary Care Hospital Experience in Gujarat (Medico Legal Update, 2021)
Background: One of the most common infections caused by protozoa in India is malaria. Malaria caseshave different geographic distribution in different areas. So it is important that hospitals in different areasdraw their own set of data regarding clinical and hematological characteristics of malaria. The present studywas conducted to evaluate the spectrum of clinical and hematological changes in patients of malaria.Material and method: We conducted retrospective study at Pathology department, Sumandeepvidyapeeth,with 55 patients aged between 5 to 75 years.Results: Out of 55, 40 were males and 15 were females. PV constituted majority of the cases, followed by PF.We reported anemia in 34 of malaria cases. Maximum cases of anemia was seen in PF. Thrombocytopeniawas seen in 42 of malaria cases. Maximum cases was seen in PV. Leucocyte count was within referencerange in majority of our cases 42.Conclusion: Fever with rigors and chills, headache and splenomegaly are the most common clinicalalteration and anemia and thrombocytopenia are most common hematological alteration in cases of malaria.Presence of these classic picture in a patient ever, helps diagnosing malaria at the earlier stages. In that way,early treatment can be introduced.